(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Near resembling faces ,Look alike faces, disguised faces and many more are todays challenges for researchers in the field of face recognition and these challenges become more serious in case of large facial Variations. Humans are able to identify reliably a large number of faces but a automated face recognition system must be face specific, it should effectively use features that discriminate a face from others by preferably amplifying distinctive characteristics of face. Face recognition has drawn wide attention from researchers in areas of machine learning, computer vision, pattern recognition, neural networks, access control, information security, law enforcement and surveillance, smart cards etc. This paper shows that how the unique face which is having a unique singular value per face under different variations is effectively classified and recognized.